1994
DOI: 10.1287/mksc.13.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence on the Negative Effect of Product Features and Sales Promotions on Brand Choice

Abstract: Sales promotions and product enhancements are commonly expected to increase a brand's sales, when they do not negatively impact its utility and cost. That is, the purchase probability of consumers who find the promotion or additional feature attractive will increase, whereas the purchase likelihood of other consumers will not be affected. In contrast, we propose that consumers, who perceive a new feature or promotion as providing little or no value, will be less likely to purchase the enhanced brand even when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
209
1
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(236 citation statements)
references
References 20 publications
10
209
1
7
Order By: Relevance
“…Another factor is whether the review provides reasons that are relevant to the reader. Just as added product features can sometimes have perverse effects and hurt brand choice among consumers who see them as irrelevant to their own interests (Simonson, Carmon, and O'Curry 1994), reviews that contain irrelevant reasons might also have perverse effects and actually lead to more positive evaluations. Future work might also examine when negative publicity boosts product evaluations.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Another factor is whether the review provides reasons that are relevant to the reader. Just as added product features can sometimes have perverse effects and hurt brand choice among consumers who see them as irrelevant to their own interests (Simonson, Carmon, and O'Curry 1994), reviews that contain irrelevant reasons might also have perverse effects and actually lead to more positive evaluations. Future work might also examine when negative publicity boosts product evaluations.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Previous research suggests that consumers evaluate offers on the basis of the perceived fit between the offer and their own resources and needs (Kivetz and Simonson 2003;Prelec et al 1997). For example, although consumers are typically attracted to products with more features (Brown and Carpenter 2000;Thompson, Hamilton, and Rust 2005), adding features that are believed to be targeted at other consumers (e.g., calculator functions only useful to biochemistry students) can actually make products less attractive (Simonson, Carmon, and O'Curry 1994). Consumers seem to actively look for cues to determine whether products are targeted to them.…”
Section: Using Frequency Cues To Infer Fitmentioning
confidence: 99%
“…The data indicate that people essentially disregard the duration of an affective episode when making retrospective assessments and that they heavily rely on just one or two moments in the episode . Simonson, Carmon, and O'Curry (1994) showed that in some cases, added features and offered promotions can lead participants to rate a brand lower, even when the features are seen as neutral or positive and the promotions are completely optional. Their research is not directly relevant to the peak-end rule in that the information about products, promotions, and /or features was available simultaneously rather than sequentially.…”
mentioning
confidence: 99%